Zoom Video Meeting as a Blended Learning Tool for Early Childhood Learning at RA Perwanida Wonosobo - Laily Mardiyati (CLLiENT (Culture, Literature, Linguistics, and English Teaching), 2020)
The current COVID-19 pandemic has reduced the stability of education in Indonesia, currently face-to-face learning is prohibited, causing learning to be impossible. If this situation continues, education will experience a slump. This situation is a very crucial problem in the world of education that really needs to be handled. In overcoming educational problems during the COVID-19 pandemic, there is a need for learning innovations that can be carried out so that education can be sustainable and the potential of children can continue to develop, including at RA Perwanida Wonosobo. This study uses a classroom action approach about zoom video meetings as a means of blended learning to improve early childhood learning at RA Perwanida. The results of classroom action research that have been carried out at RA Perwanida Wonosobo are: 1). The activity of children in learning zoom meeting as a means of blended learning in the first cycle was 69% and increased to 89% in the second cycle. 2). Completeness of children in the first cycle is 67% and in the second cycle is 86% based on the results in cycle I and cycle II, we can conclude that learning through zoom video meetings as a means of blended learning can improve early childhood learning at RA Perwanida. Keywords: zoom video meeting; blended learning.